The epidemiological survey for atovaquone resistant related gene of Babesia gibsoni in Japan - IGUCHI, Aiko; SOMA, Takehisa; SUZUKI, Hiroshi; XUAN, Xuenan (Journal of Veterinary Medical Science, 2016)
In 73 gDNA samples from Babesia gibsoni-infected dogs, the M121I variant population was measured by using allele-specific real-time PCR. Although the mechanism of atovaquone against B. gibsoni has not been clearly identified, it is reported that the mitochondria cytochrome b gene of the atovaquone-resistant B. gibsoni had a single-nucleotide substitution at nt363 (G to T), which resulted in the substitution of methionine with isoleucine (M121I). In this study, 3/73 samples showed over 5% M121I variant population. Although the M121I variant population is a low percentage, it runs the risk of spreading drug-resistant parasites. It is important to prevent the spread of drug-resistance, so we need to gather information about this at regular intervals.